The long march of European history (2020)
These days, the social sciences must circulate through the Islamic, African, Asian, and occidental worlds because the European discourse can no longer be seen as the universal discourse. In 1517, more than 500 years ago, the Lutheran Reformation fractured Europe. That very same year, the Spanish conquistadors took over Mexico, colonizing and christianizing it. They also introduced the way in which we write history. The conquerors were completely ignorant about the indigenous societies. However, in order to impose their laws, they had to learn about their customs and, therefore, the past of those they conquered. But, what is history and time in the mind of the indigenous peoples? Time was not yet a universal value. How could the Spaniards, formed in a Christian Europe where history was chronological and focused, understand and accept Mesoamerican cosmology? The civilized against barbarians? In a few decades, the «time machine» of the invadors was used to capture the memories of the Amerindian native societies in order to fabricate a past that could be linked with the ancient heritage of Christianity. The author offers an original exploration of the beginning of the colonial expansion and explains how across the territory, the religious and the indigenous peoples began to write a history of the world.